COCA CORPUS AND ITS COMPONENTS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This article provides detailed information about the COCA (The Corpus of Contemporary American English ) corpus and its components. The content of the corpus is analyzed from the followig point of views as number of words , type , and genres and others The method used in carrying out the study is descriptive analysis method. The result of the research demonstrates that there are collocational competence of EFL students, history of the CL , genres in the COCA corpus.